Impact and Abrasion Power Modeling of a Tumbling Mill for Control Design - Ventura-Hinostroza, H.; Sotomayor-Moriano, J.; Oliva-Moncunill, J. (Elsevier, 2023)
In this research, the model of the net power draw of a tumbling mill is proposed, which is described considering the contribution of the impact power and the abrasion power separately. Nowadays, in phenomenological models used in mill control design, the net power draw in the grinding of the mineral is not described by a dynamic representation (but by experimental formulation); therefore, the validity of the model thus obtained is restricted to a given operating condition. The proposed model describes the dynamics of the impact power and the abrasion power through variables and parameters that depend on the operating conditions, therefore this model is obtained for a whole range of operation, also it is represented in the state space, which will facilitate the control design task of the milling process. Finally, simulation tests were carried out for a tumbling mill using the proposed approach.
Keywords: Mathematical model; Impact power; Milling process; Grinding media; Tumbling mill; https://purl.org/pe-repo/ocde/ford#2.07.05